Kinerja Tutor Terhadap Kepuasan Mahasiswa Pada Tutorial Webinar (TUWEB) PGSD UPBJJ-UT Makassar Di Kabupaten Wajo - Kadariah, Kadariah; Hasmiah, Hasmiah; B, M. Jafar; Sukarman, Sukarman (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2021)
This study aims to explain the correlation between tutor performance and the level of student satisfaction in the webinar tutorial (Tuweb). This study uses two approaches, namely quantitative and qualitative approaches. Data were analyzed using simple linear regression analysis. The sampling technique was simple random sampling of 40 people. The regression coefficient value is 0.144, this means that if the tutor's performance has increased by one unit, the level of student satisfaction in the UPBJJ-UT Makassar webinar (Tuweb) tutorial in Wajo Regency increases by 0.144 units. The determination coefficient test (KD) or the R2 test is 0.598 or 59.8%, which means that the effect of tutor performance on student satisfaction on webinar tutorials (Tuweb) is 59.8%. The results of the analysis and processing of research data show that there is a positive and significant influence between tutor performance on student satisfaction in the PGSD UPBJJ-UT Makassar webinar tutorial in Wajo Regency. This means that it is very supportive of the learning conditions during the Covid-19 pandemic, which really requires all sectors and fields, especially in the field of education, which demands to continue to innovate to promote online or online learning systems